TIVENESS AND EFFICIENCY OF THE SYSTEM OF PROTECTED NATURAL AREAS (Scientific journal of the Fergana State University, 2023)
In this article, the system of protected natural areas (PNA) is considered as a reliable tool for the conservation and protection of biological and landscape diversity, ensuring sustainable use, and maintaining environmental stability. To create a protected area system capable of practically fulfilling the above goals and objectives, its comprehensive assessment from a geoecological point of view is required. Such an assessment process is extensive and complex, and there are no uniform criteria and methods developed that satisfy all specialists in this field. Therefore, attention was paid to assessing the representativeness and effectiveness of the existing system of specially PNA. This approach makes it possible to determine the possibilities for future improvement of the existing system of PNA.